Soil properties and silage quality in response to oat and pea seeding ratios and harvest stage on the Qinghai-Tibetan Plateau - Liu, Wen; Zhao, Liansheng; Chen, Yakun; Shen, Yifan; Luo, Zhijie; Chen, Yanbin; Evans, Alexander C. O.; Bu, Dengpan (Frontiers in Sustainable Food Systems, 2023)
Livestock intensification improves production efficiency and enhances the demand for quality forage to feed ruminants. Novel combinations of forage plants, especially including Gramineae and Leguminous plants, benefit both ruminant animals and contribute to a sustainable environment. This study explored an oat-pea mixed seeding strategy as an approach to improving silage quality. Before ensialing, lactic acid bacteria (Lactobacillus plantarum and Lactobacillus brucelli) were added to forage from five different mixed seeding proportions of oats (O) and peas (P) (10:0, 8:2, 7:3, 5:5, and 0:10 oat to pea ratio) at two harvesting periods (the early flowering stage and the milk ripening stage for the oats). The results showed that mixed seeding changed the soil quality parameters. Moreover, the silage from the O5P5 (5:5 oat to pea ratio) group showed the lowest pH values (4.16) and highest LA contents (7.74% DM) after ensiling for 7d (p < 0.05) in early flowering stage. Also, the O5P5 group increased the number of tillers/branches and produced silage with the highest CP content (13.14–14.06) after ensiling for 7d in early flowering stage and both 7d and 30d in early flowering stage and milk ripening stage (p < 0.05). In conclusion, this study found that the selection of oat-pea mixed seeding as O5P5 and harvesting at the milk ripening stage of oat is recommended as a desirable oat-pea mixed seeding strategy for producing high quality silage.